Pengaruh Penerapan Customer Relationship Management terhadap Keberlanjutan Perusahaan dengan Eco-Friendly Marketing sebagai Variabel Mediasi - Robert Jao; Suwandi Ng; Anthony Holly; Erica Honasan Ho; Jamaluddin Majid (Universitas Muhammadiyah Sorong, 2023)
The purpose of the study is to investigate the influence of customer relationship management on eco-friendly marketing, customer relationship management on corporate sustainability, eco-friendly marketing on corporate sustainability, and customer relationship management on corporate sustainability through eco-friendly marketing. This research uses purposive sampling method in sample selection. The sample used is retail companies in Makassar City, South Sulawesi. Total Sample is 84 respondents. The data collection method used is survey with questionnaire. The analysis techniques used is path analysis. The results show that customer relationship management has a positive and significant impact on eco-friendly marketing, customer relationship management has a positive and significant impact on corporate sustainability, eco-friendly marketing has a positive and significant impact on corporate sustainability, and eco-friendly marketing mediates the effect of customer relationship management on the corporate sustainability.